Basel Compliance and Financial Stability : Evidence from Islamic Banks - Bitar, Mohammad; Ayadi, Rym.; Ben Naceur, Sami.; Walker, Thomas (Washington, D.C. : International Monetary Fund, 2017)
The paper provides robust evidence that compliance with Basel Core Principles (BCPs) has a strong positive effect on the Z-score of conventional banks, albeit less pronounced on the Zscore of Islamic banks. Using a sample of banks operating in 19 developing countries, the results appear to be driven by capital ratios, a component of Z-score for the two types of banks. Even though smaller on Islamic banks, individual chapters of BCPs also suggest a positive effect on the stability of conventional banks. The findings support the effective role of BCP standards in improving bank stability, whose important implications led to the Islamic Financial Services Board (IFSB) publication of new recommendations in 2015 to bring BCP standards in line with the Core Principles for Islamic Finance Regulation (CPIFRs) standards. Our findings suggest that because Islamic banks are benchmarked closely to BCPs, the implementation of CPFIRs should also positively affect their stability.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet